The measurement of reactive oxygen species in human neat semen and in suspended spermatozoa: a comparison - Fingerova, Helena; Oborna, Ivana; Novotny, Jiri; Svobodova, Magda; Brezinova, Jana; Radova, Lenka (Reproductive biology and endocrinology, 2009)
BACKGROUND: It is generally accepted that oxidative stress is an important factor in male infertility because it may impair the physiological function of spermatozoa at the molecular level. Nevertheless, although several approaches have been reported, the imbalance between production of reactive oxygen species (ROS) and activity of the antioxidant defense system in semen is difficult to investigate and remains poorly understood. METHODS: This study compares measurement of ROS production in neat semen and in washed spermatozoa obtained from the same ejaculate, and suspended in phosphate buffered saline using exactly the same luminol-mediated chemiluminescence method. Ninety one samples were obtained from males of infertile couples and 34 from volunteers with proven fertility. RESULTS: As expected, ROS levels were markedly lower in neat semen than in washed spermatozoa suspensions where seminal plasma with its potent antioxidant capacity was removed. In the cases of both neat semen and washed spermatozoa, ROS production was lowest in samples from normozoospermic males and highest in samples containing more than half million peroxidase-positive leukocytes per milliliter. For all samples, there was a significant positive correlation between ROS production by neat semen and that by washed spermatozoa suspension. CONCLUSION: Measurement of ROS production in neat semen better reflects actual oxidative status because it detects only the overproduction of ROS which are not effectively scavenged by antioxidant capacity of seminal fluid. The results of our study show a good commutability of both measurements for identification of semen samples with high ROS production. The measurement in neat semen is even less time consuming and therefore easier to implement into laboratory routine.
Keywords: Semen Preservation; uchování spermatu; Sperm Retrieval; odběr spermií; Sodium Chloride; sperma; Reactive Oxygen Species; pomocné látky; Excipients; Male; Semen Analysis; Semen; lidé; mužské pohlaví; Humans; reaktivní formy kyslíku; chlorid sodný; analýza spermatu